Flow and heat transfer of petal-shaped double tube (Water and air-water bubbly flow) - Toshihiko SHAKOUCHI (The Japan Society of Mechanical Engineers, 2016)
Heat exchangers are widely used for heating, cooling, evaporation, and condensation. There are many types of heat exchangers, shell and tube, fin tube, and double tube heat exchangers. Double tube heat exchangers show high performance, and several modifications have been made with regard to their pipe geometry to further improve their performance. A petal-shaped double tube with a large wetted perimeter is one such example. The working fluid of a heat exchanger for the evaporator and condenser of an air-conditioner or boiler may become a gas-liquid two-phase flow with phase change. In this study, the flow and heat transfer characteristics of air-water bubbly flow through a petal-shaped double tube with a large wetted perimeter are examined experimentally and compared with those of a conventional circular double tube. The experiments employed two petal-shaped double tubes: one with six petals and another with five petals. This study explains for single-phase water and two-phase air-water bubbly flows. The heat transfer characteristics are studied by measuring the temperature distributions in the inner and outer pipes by a thermo couple. The study also clarifies the effects of air bubbles on heat transfer performance.